Interdisciplinary study on valuation systems and evidentiary standards in Colombian procedural law - Rivera Olarte, Francisco Javier; Rojas Quinayá, Lina Fernanda (DIXI, 2019)
Purpose: The purpose of this research is to conduct an interdisciplinary study on the legal, doctrinal and jurisprudential framework of evaluation systems and standards of evidence in Colombian procedural law, in order to determine their application by judges at the time of adjudication. Methodology: The development of the present proposal is framed in the type of legal research since it intends, from a normative and interdisciplinary study (procedural law), to review the subject of the valuation systems and the standard of evidence. Likewise, it is based on the deductive and analytical-descriptive method. Finally, the applied technique is the documentary technique. Results and conclusions: First, nowadays, procedural law of evidence is based on “healthy criticism” as a system for evaluating the evidence. Second, in Colombia, the law of criminal evidence, in Article 381 of the Political Constitution, enunciates that the standard of proof consists of “knowledge beyond all doubt”. Third, procedural law of evidence has not developed the elements of healthy criticism, nor the standards of proof to be applied, which are empty norms that need to be filled in through doctrine and jurisprudence.